2005
DOI: 10.1038/nature04224
|View full text |Cite
|
Sign up to set email alerts
|

Towards complete cofactor arrangement in the 3.0 Å resolution structure of photosystem II

Abstract: Oxygenic photosynthesis in plants, algae and cyanobacteria is initiated at photosystem II, a homodimeric multisubunit protein-cofactor complex embedded in the thylakoid membrane. Photosystem II captures sunlight and powers the unique photo-induced oxidation of water to atmospheric oxygen. Crystallographic investigations of cyanobacterial photosystem II have provided several medium-resolution structures (3.8 to 3.2 A) that explain the general arrangement of the protein matrix and cofactors, but do not give a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

102
2,087
5
12

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,812 publications
(2,206 citation statements)
references
References 29 publications
102
2,087
5
12
Order By: Relevance
“…Only within the last three years, has the structural arrangement of each subunit, with respect to each other, been resolved by X-ray crystallography to 3-3.5 Å resolution with considerable certainty (Rfactor = 24 %) [16,17]. PSII isolated from Thermosynechococcus sp.…”
Section: Photosystem Ii: a Structural Snapshotmentioning
confidence: 99%
“…Only within the last three years, has the structural arrangement of each subunit, with respect to each other, been resolved by X-ray crystallography to 3-3.5 Å resolution with considerable certainty (Rfactor = 24 %) [16,17]. PSII isolated from Thermosynechococcus sp.…”
Section: Photosystem Ii: a Structural Snapshotmentioning
confidence: 99%
“…If this assignment is correct (see Chu et al 2001), the latest information from X-ray crystallography (Loll et al 2005b) suggests that the bridging carboxylate could be D1 Glu 189 or Ala 344, but neither of these would agree with the FTIR data (Strickler et al 2005(Strickler et al , 2006. Noguchi et al (1995) concluded from the overall suppression of the S 1 to S 2 FTIR changes that Ca 2+ depletion makes this carboxylate dissociate from manganese as well, but since their sample was probably in the S 1 (K + ) state (Kimura and Ono 2001), we would conclude that no S 1 to S 2 transition occurred.…”
Section: S 1 To S 2 Transitionmentioning
confidence: 99%
“…The most recent example is shown in Fig. 1, taken from Loll et al (2005b). It is now known, that all of the published structures are compromised by radiation damage to the Mn cluster of the OEC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations